PENERAPAN METODE PROMETHEE PADA SISTEM PENDUKUNG KEPUTUSAN REKOMENDASI LOKASI PENDIRIAN FASILITAS KESEHATAN - Muhammad Ikhlas; Masriadi (Biomedical and Environmental Health Technology, 2026)
Advancements in information technology have made significant contributions to supporting decision-making processes across various sectors, including healthcare. One of the major challenges faced by governments and related agencies is determining the most appropriate locations for healthcare facilities to ensure that healthcare services are delivered equitably, effectively, and in accordance with community needs. This study aims to implement the PROMETHEE method in a web-based Decision Support System (DSS) to assist in recommending suitable locations for healthcare facility establishment based on multiple evaluation criteria. The PROMETHEE method is employed to analyze and compare alternative locations using criteria such as distance to the health department office, population density, accessibility, establishment cost, and proximity to existing healthcare facilities. The developed system automatically calculates the leaving flow, entering flow, and net flow values, thereby generating an objective ranking of alternative locations. The results indicate that Alternative 2 (A2) achieved the highest Net Flow value of 0.56, outperforming Alternative 1 (A1) and Alternative 3 (A3). Consequently, the system successfully recommends the most appropriate location for establishing a healthcare facility based on the highest net flow value. Therefore, the proposed system effectively supports decision-making in a more objective, systematic, accurate, and efficient manner, serving as a reliable reference for planning the development of healthcare facilities in suitable locations.